In organello footprint analysis of human mitochondrial DNA: human mitochondrial transcription factor A interactions at the origin of replication. - Steven C. Ghivizzani; C S Madsen; Marcel Nelen; Chandramohan V. Ammini; William W. Hauswirth (1994)
Using in organello footprint analysis, we demonstrate that within human placental mitochondria there is a high level of protein-DNA binding at regularly phased intervals throughout a 500-bp region encompassing the D-loop DNA origins and two promoter regions. Comparison with in vitro DNase I protection studies indicates that this protein-DNA interaction is due to non-sequence-specific binding by human mitochondrial transcription factor A (h-mtTFA). Since h-mtTFA can bend and wrap DNA, like its yeast counterpart ABF2, a primary function of h-mtTFA appears to be specific packaging of the mitochondrial DNA control region in vivo. Intervals of protein binding coincide with the spacing of the RNA start sites and prominent D-loop DNA 5' ends, suggesting a role for phased h-mtTFA binding in defining transcription and H-strand DNA replication origins. Significant protein-DNA interaction was also observed within the human homolog of conserved sequence block 1, both in organello and in vitro, using purified h-mtTFA.